2019
DOI: 10.1097/sla.0000000000002628
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Mortality After Nonelective Surgery for Inflammatory Bowel Disease Patients in the Era of Biologics

Abstract: Although nonelective IBD surgery rates have remained stable, associated 30-day mortality for UC has doubled in recent years despite advances in medical management. Current clinical decision-making and care pathways must be further evaluated to improve outcomes in this high-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 28 publications
1
23
0
1
Order By: Relevance
“…Fourteen per cent of all operated patients had complications requiring surgical, endoscopic and/or radiological intervention and five (4%) patients eventually died . Emergency surgery increased the risk of early post‐operative complications, odds ratio 4.46 (95% confidence interval 1.75‐11.36), and similar findings regarding emergency surgery has been shown previoulsy . An English study on emergency colorectal surgery found the 30‐day mortality risk to be four‐times greater compared with scheduled procedures .…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…Fourteen per cent of all operated patients had complications requiring surgical, endoscopic and/or radiological intervention and five (4%) patients eventually died . Emergency surgery increased the risk of early post‐operative complications, odds ratio 4.46 (95% confidence interval 1.75‐11.36), and similar findings regarding emergency surgery has been shown previoulsy . An English study on emergency colorectal surgery found the 30‐day mortality risk to be four‐times greater compared with scheduled procedures .…”
mentioning
confidence: 58%
“…In Denmark the total 30‐day mortality was 1.0% after elective subtotal colectomy compared with 5.3% in emergency subtotal colectomy, while in patients ≥60 years the corresponding risks were 3.3% and 18.4% . A recent report from Justiniano et al looked into the outcome of IBD‐related surgery in the state of New York 2000‐2013 . The 30‐day mortality was 0.4% in CD and 0.6% in UC in elective surgery and increased to 2.7% and 12.9%, respectively, in emergency surgery and increased with every 10‐year age increment of patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subtotal colectomy with ileostomy and preservation of the rectal remnant is the preferred surgical treatment for patients with acute severe colitis refractory to medical treatment (1,2). In Sweden, the postoperative mortality rate after elective surgery is about 1%, but recent studies have shown mortality rates as high as 12.9% (3,4) after emergency colectomies. The morbidity after surgery is high, especially after emergency surgery, with figures about 30%-40% (2,(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…The 30‐day mortality was zero in this study but we need to watch out and work in close collaboration with our gastroenterologists. We do not want results like those in the recent publication on non‐elective surgery in IBD from the state of New York with a 30‐day mortality of 2.7% in Crohn's disease and 12.9% in ulcerative colitis .…”
mentioning
confidence: 99%